2003
DOI: 10.1023/b:cyto.0000039917.60348.45
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carvacrol on a Human Non-Small Cell Lung Cancer (NSCLC) Cell Line, A549

Abstract: Carvacrol, the predominant monoterpene in many essential oils of Labitae including Origanum, Satureja, Thymbra, Thymus, and Corydothymus has substantial antibacterial, antifungal, antihelmintic, insecticial, analgesic and antioxidant activities. Approximately 75% of lung cancer is non-small cell carcinoma (NSCLC) which comprises several histologic types squamous cell, adenocarcinoma and large cell carcinoma. It was reported that the portion of lung tumors diagnosed as denocarcinoma has increased. Thus a human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(61 citation statements)
references
References 11 publications
4
56
0
1
Order By: Relevance
“…Carvacrol and thymol signifi cantly reduced the level of DNA damage induced in K-562 cells by the strong oxidant H 2 O 2 (Horvathova et al, 2007). Furthermore, carvacrol has an important in vitro antitumor effect against tumor cell lines like Hep-2 (Stammati et al, 1999), B16 (He et al, 1997) and A-549 (Zeytinoglu et al, 2003;Tansu Koparal & Zeytinoglu, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carvacrol and thymol signifi cantly reduced the level of DNA damage induced in K-562 cells by the strong oxidant H 2 O 2 (Horvathova et al, 2007). Furthermore, carvacrol has an important in vitro antitumor effect against tumor cell lines like Hep-2 (Stammati et al, 1999), B16 (He et al, 1997) and A-549 (Zeytinoglu et al, 2003;Tansu Koparal & Zeytinoglu, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, carvacrol, a component of thyme essential oil, is one of natural products with important biological activities. It has been reported to have an important antitumor effect (Jaafari et al, 2007(Jaafari et al, , 2009Zeytinoglu et al, 2003). The combination of these molecules with conventional drugs could have a synergistic effect (Wiseman et al, 2007;Chander et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Ipek et al [35] found that carvacrol prevented mutagenicity of known mutagens in lymphocytes and inhibited the DNA synthesis in mouse myoblasts. Koparal and Zeitinoglu [36] reported that carvacrol applied A549 cell lines, increase in dose of carvacrol caused a decrease in cell number, degeneration of cell morphology and a decrease in total protein amount. Cells were treated with carvacrol were seen to have detached from the disk, with cell rounding, cytoplasmic blebbing and irregularity in shape.…”
Section: Monoterpenes and Anticarcenogenesis Activitymentioning
confidence: 99%
“…Cell morphology consistent with apoptosis and a remarkable activation of caspase-3 were also observed, suggesting induction of caspase-dependent apoptotic cell death. Carvacrol, one of the members of monoterpene phenols present in the volatile oils of T. vulgaris, inhibited viability and proliferation of A549 cells, a human non-small cell lung cancer, and induced early apoptotic features in a dose-dependent manner [94]. In the study conducted by Yin et al [100], carvacrol affected apoptosis of human hepatoma HepG2 cells by the activation of caspase-3, cleavage of PARP and decreased Bcl-2 gene expression.…”
Section: Salvia Officinalis Salvia Officinalis L (Common Sagementioning
confidence: 99%
“…As observed, extracts with higher antioxidant capacity had also higher polyphenol contents. Additionally, carvacrol inhibited 7,12-dimethylbenz(a)anthracene (DMBA) induced tumorigenesis in rats [92], growth of murine B16 melanomas [93] and human non-small lung cancer A549 cell line [94], while thymol significantly increased activities of antioxidant enzymes such as SOD and GPx in rats [95].…”
Section: Salvia Officinalis Salvia Officinalis L (Common Sagementioning
confidence: 99%